Assessment of apoptotic mediators in different periodontal plights: apoptosis markers in periodontal diseases - Asem Mohammed Kamel Ali; Bahaa M. Badr; Abdullah I. Ali; Mohamoud A. Mizer; Ahmed M. Abdelrahman; Asmaa Rashad Ali; Abdel-Moneim M. I. Ghorab; Mohammed G. M. El Sherbeny; Azza A. Althoqapy (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2026)
Background: Highly expressed apoptosis markers in an inflammatory condition were observed following periodontal breakdown with obscure lineaments. Purpose: This trial aimed to assess the gingival crevicular fluid (GCF) level of caspase-3, -8, -9, and apoptosis-inducing factor (AIF) in various periodontal conditions. Methods: These investigations were conducted on 50 contributors whose conditions were classified as follows: Group 1—clinically healthy gingiva; Group 2—mild periodontitis (Stage 1, Grade A); Group 3—moderate periodontitis (Stage 2, Grade A); Group 4—severe periodontitis (Stage 3, Grade A); Group 5—very severe periodontitis (Stage 4, Grade C). Quantities of caspase-3, -8, -9, and AIF were estimated in GCF by enzyme-linked immunosorbent assay. Results: In-between group dissimilarities were compared by analysis of variance. Correlations among caspase-3, -8, -9, AIF standards, and clinical periodontal variables were observed by Spearman’s rank correlation analysis. When comparing Stage 4, Grade C periodontitis with Stage 3, Grade A periodontitis, there was a statistically significant difference in all clinical variables. The caspase-3 level of 10.5 ± 3.68 ng/ml in the healthy group reached 37.5 ± 5.14 ng/ml in the periodontitis Stage 4, Grade C group; the caspase-8 level of 11.24 ± 2.59 ng/ml in the healthy group reached 32.63 ± 4.8 ng/ml in the periodontitis Stage 4, Grade C group; the caspase-9 level of 40.61 ± 14.2 ng/ml in the healthy group reached 89.47 ± 21.3 ng/ml in the periodontitis Stage 4, Grade C group; the AIF level of 207 ± 63.98 ng/ml in the healthy group reached 1,992 ± 454.5 ng/ml in the periodontitis Stage 4, Grade C group. Only caspase-9 and AIF can differentiate between periodontitis Stage 3 and periodontitis Stage 4. Conclusion: A positive correlation between apoptotic biomarkers and the progression of periodontal diseases was observed. An increased level of apoptotic factors in Stage 3, Grade A and Stage 4, Grade C periodontitis suggests an influential role of lysosomal enzymes in the pathogenesis of periodontitis.